PENGARUH MODEL PEMBELAJARAN IDEA (ISSUE, DISCUSSION, ESTABLISH, AND APPLY) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP STATISTIKA - Fatmawatie, Ika A’izzah; Wulandari, Tri Candra; Ilmi, Yuli Ismi Nahdiyati (EDUPEDIA, 2024)
The aims of this study is to determine whether there is an effect of the IDEA (Issue, Discuss, Establish, and Apply) learning model on the ability to understand concepts in students of class VIII Islamic Pakis Junior High School statistics material. This study uses a quantitative approach with a quasi experiment design method and a non-equivalent control group design. The population in this study were all students in grade VIII of SMP Islam Pakis in the 2023/2024 school year. The method used for sampling is saturated sampling method. The instrument used is a test, before the instrument is used in the learning process, the researcher must test its validity. The validity test in this study uses content validity. The data collection procedure used by researchers begins with a pretest, the implementation of learning or giving treatment, and ends with a posttest. The data analysis technique used in this study is parametric analysis using the independent sample t-test test. Before using the independent sample t-test test, researchers used 2 prerequisite tests, namely, normality and homogeneous tests. The results of the normality test and homogeneous test both show sig.0.05, which means that the data obtained are normally distributed and from homogeneous samples, so data analysis can be carried out using the Independent sample t-test test with a significance level of 0.05. The results of the pre-test and post-test data analysis from the control and experimental classes showed that there was an effect of learning using the IDEA model on concept understanding ability with Sig. = 0.00 (sig 0.05).